miR–9-5p regulates immunometabolic and epigenetic pathways in β-glucan–trained immunity via IDH3α - Haibo Su; Zhongping Liang; ShuFeng Weng; Chaonan Sun; Jiaxin Huang; TianRan Zhang; Xialian Wang; Shanshan Wu; Zhi Zhang; Yiqi Zhang; Qing Gong; Ying Xu (JCI Insight, 2021)
Trained immunity, induced by β-glucan in monocytes, is mediated by activating metabolic pathways that result in epigenetic rewiring of cellular functional programs; however, molecular mechanisms underlying these changes remain unclear. Here, we report a key immunometabolic and epigenetic pathway mediated by the miR–9-5p-isocitrate dehydrogenase 3α (IDH3α) axis in trained immunity. We found that β-glucan–trained miR–9-5p–/– monocytes showed decreased IL-1β, IL-6, and TNF-α production after LPS stimulation. Trained miR–9-5p–/– mice produced decreased levels of proinflammatory cytokines upon rechallenge in vivo and had worse protection against Candida albicans infection. miR–9-5p targeted IDH3α and reduced α-ketoglutarate (α-KG) levels to stabilize HIF-1α, which promoted glycolysis. Accumulating succinate and fumarate via miR–9-5p action integrated immunometabolic circuits to induce histone modifications by inhibiting KDM5 demethylases. β-Glucan–trained monocytes exhibited low IDH3α levels, and IDH3α overexpression blocked the induction of trained immunity by monocytes. Monocytes with IDH3α variants from autosomal recessive retinitis pigmentosa patients showed a trained immunity phenotype at immunometabolic and epigenetic levels. These findings suggest that miR–9-5p and IDH3α act as critical metabolic and epigenetic switches in trained immunity.